Pesan pada Puisi Negeri di Tepi Jurang Karya Fadli Zon - Reynol Moha; Herson Kadir; Ellayana Hinta (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to determine the message of democracy, economics, morals, and religion in the poem Negeri di Tepi Jurang by Fadli Zon. The approach in this research is qualitative with descriptive analysis method. The research results show that 1) the message of democracy is that people don t get space for freedom, their aspirations are no longer heard, 2) the message of the economy is that the nation is in debt, and has been hit by a pandemic, accompanied by disasters that have caused social inequality to occur, 3) the moral messages are lies, hatred, hypocrisy, and oppression is a series of moral degradation, which is contrary to the noble values of the nation, 4) Religious messages contain expressions of prayers of hope for the problems that hit the country.